sqrt(x-1)+x=7

Simple and best practice solution for sqrt(x-1)+x=7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for sqrt(x-1)+x=7 equation:


Simplifying
sqrt(x + -1) + x = 7

Reorder the terms:
qrst(-1 + x) + x = 7
(-1 * qrst + x * qrst) + x = 7
(-1qrst + qrstx) + x = 7

Solving
-1qrst + qrstx + x = 7

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-1qrst + qrstx + x + -1x = 7 + -1x

Combine like terms: x + -1x = 0
-1qrst + qrstx + 0 = 7 + -1x
-1qrst + qrstx = 7 + -1x

Reorder the terms:
-7 + -1qrst + qrstx + x = 7 + -1x + -7 + x

Reorder the terms:
-7 + -1qrst + qrstx + x = 7 + -7 + -1x + x

Combine like terms: 7 + -7 = 0
-7 + -1qrst + qrstx + x = 0 + -1x + x
-7 + -1qrst + qrstx + x = -1x + x

Combine like terms: -1x + x = 0
-7 + -1qrst + qrstx + x = 0

The solution to this equation could not be determined.

See similar equations:

| 2.5+.075p=.01p | | 5ln(2x-2)+10=0 | | X^2+13x-31=7x-4 | | 20x+10=5*20 | | 2.1x-8.1=3.16-5.4x | | 2p^2/5-p^1/5-1=0 | | H(t)=-10t^2+10t+24 | | .05x+.06(3x)=943 | | 5y-3+y+29=5y+30-1y | | .6n-.6=6n+1.3 | | 3x+20=8x-40 | | 6g+18=9g-25 | | -7-7(4x+8)=-175 | | a-a^1/2-6=0 | | 3x+20=4x-5 | | a-a^1/2-6= | | 9r^2=18 | | g−3/7=2/7​​ | | 12-3(3-3x)=6x | | -235=.05(x)-.06(x) | | |x/2-3|-5-2 | | 3z/10-9=-8 | | 7a-1=4(3a+6) | | 14x-9=13x+51 | | 3/x-2=1/x | | 4/56 | | 3(4x+5y)=12 | | sqrt(x^2-3x)=2 | | -6+7(x-3)=37-x | | .08(x)+.12(x+250)=348 | | x+0.13x=3500 | | X^2-18x-31=0 |

Equations solver categories